Hypothesis and Theory: Fungal Spores in Stemflow and Potential Bark Sources - Magyar, Donát; Van Stan, John T.; Sridhar, Kandikere R. (Frontiers in Forests and Global Change, 2021)
The study of stemflow fungi began over 50 years ago. Past work has been performed in different climatic regions of the world, with different sampling methods, by mycologists focusing on different taxonomical groups. Therefore, we aim to synthesize this work to delineate major conclusions and emerging hypothesis. Here, we present: (1) a systematic compilation of observations on stemflow conidial concentration, flux and species composition; (2) an evaluation of the methods underlying these observations; (3) a testable theory to understand spatiotemporal dynamics in stemflow (including honeydews) conidial assemblages, with a focus on their relationship to bark structure and microhabitats; and (4) a discussion of major hypotheses based on past observations and new data. This represents a knowledge gap in our understanding of fungal dispersal mechanisms in forests, in a spatially-concentrated hydrologic flux that interacts with habitats throughout the forest microbiome. The literature synthesis and new data represent observations for 228 fungal species’ conidia in stemflow collected from 58 tree species, 6 palm species, and 1 bamboo species. Hypothetical relationships were identified regarding stemflow production and conidial concentration, flux, and species composition. These relationships appear to be driven by bark physico-chemical properties, tree canopy setting, the diversity of in-canopy microenvironments (e.g., tree holes, bark fissures and epiphytes), and several possible conidia exchange processes (teleomorph aerosols, epi-faunal exchanges, fungal colonization of canopy microhabitats, droplet impacts, etc.). The review reveals a more complex function of stemflow fungi, having a role in self-cleaning tree surfaces (which play air quality-related ecoservices themselves), and, on the other hand, these fungi may have a role in the protection of the host plant.